Reflective practice in Nursing Students: The undervalued cognitive skill that needs to be consolidated - Kaur, Ekjot (Journal of Gandaki Medical College-Nepal, 2026)
Reflection has been recognized, during the recent years as a vital skill to improve the clinical and professional performances of nurses. It involves the precise analysis of a clinical situation or condition, through careful and detailed review of feelings, actions, thoughts and behaviors. Different nursing programmes should encourage the development and use of reflective practices among the students. Administrators should consider constructing and designing the curriculum which enhances this skill among the students, thus improving their self learning and efficacy. Students should be encouraged to write and practice reflective exercises, which should be integrated with the development of other competencies. The instructors should address the gaps and encourage the students to work on the areas that need improvement. Mentorship can be planned for the students with weaker reflective capacity.